Antimony/N‐Hydroxyphthalimide as a Catalyst System for Cross‐Dehydrogenative Coupling Reactions under Aerobic Conditions. Issue 2 (1st February 2013) - Tanoue, Arata; Yoo, Woo‐Jin; Kobayashi, Shū
Abstract In the course of our investigations to find a novel catalyst for the cross‐dehydrogenative coupling (CDC) reaction, it was discovered that antimony(V) serves as a co‐catalyst with N‐hydroxyphthalimide (NHPI) under aerobic conditions. This is a rare example of a catalytic use of antimony for an oxidative coupling reaction.